2019
DOI: 10.1002/kjm2.12098
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of tacrolimus‐based treatment for nephrotic idiopathic membranous nephropathy in young adults: A retrospective study

Abstract: In China, the prevalence of idiopathic membranous nephropathy (IMN) is increasing with a younger age of onset. From January 2012 to October 2018, biopsy‐proven nephrotic IMN patients aged between 15 and 40 in Taian City Central Hospital treated with tacrolimus (TAC) were retrospectively analyzed. Twelve‐month follow‐up data were collected. A total of 86 patients were enrolled in this study. Forty patients in the TAC group received TAC monotherapy with an initial dose of 0.05 to 0.1 mg/kg/day. Forty‐six patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…Thus, TAC can reduce urinary protein excretion and is widely used in the treatment of nephrotic syndrome. A number of studies have shown that TAC, either monotherapy or in combination with low-dose corticosteroids, was effective in treating iMN patients [ 9 , 27 , 28 ]. Praga et al used TAC monotherapy in iMN patients with normal kidney function and mean proteinuria over 12 months with a 6-month taper and compared them to conservation-treated patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, TAC can reduce urinary protein excretion and is widely used in the treatment of nephrotic syndrome. A number of studies have shown that TAC, either monotherapy or in combination with low-dose corticosteroids, was effective in treating iMN patients [ 9 , 27 , 28 ]. Praga et al used TAC monotherapy in iMN patients with normal kidney function and mean proteinuria over 12 months with a 6-month taper and compared them to conservation-treated patients.…”
Section: Discussionmentioning
confidence: 99%
“…After 18 months, the total remission rate was 94% in the TAC group, but only 35% in the control group [ 9 ]. A retrospective study by Zhao Hu et al recently showed that both TAC monotherapy and TAC combined with medium-dose prednisone in young patients aged between 15 and 40 years for 12 months led to 77.5%-80.4% remission rates [ 27 ].Thus, the KDIGO 2012 glomerular diseases guideline included TAC as one of the first-line immunosuppressive treatments for iMN patients [ 11 ], and KDIGO 2021 continued this proposition [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some patients may have PR or CR after 6 months. In the included studies of Shang Shunlai and Zhang Xiaojuan, after TAC monotherapy or combination therapy, the TR at the tenth to twelfth month was higher than the TR at the sixth month [15,17] . However, TAC monotherapy had similar TR compared with TAC-corticosteroid combination therapy at the tenth to twelfth month [15,17] .…”
Section: Discussionmentioning
confidence: 99%
“…In the included studies of Shang Shunlai and Zhang Xiaojuan, after TAC monotherapy or combination therapy, the TR at the tenth to twelfth month was higher than the TR at the sixth month. [ 15 , 17 ] However, TAC monotherapy had similar TR compared with TAC-corticosteroid combination therapy at the tenth to twelfth month. [ 15 , 17 ] More studies are needed to prove that TAC-corticosteroid combination therapy may have stronger immunosuppressive effects than TAC monotherapy for IMN.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation